PERAMALAN JUMLAH PENUMPANG DOMESTIK DI YOGYAKARTA INTERNATIONAL AIRPORT - Subandi, Subandi (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
This research is quantitative descriptive research which aims to make predictions using the ARIMA model time series forecasting method. The data obtained was analyzed using the R program. The data used for forecasting is the number of arrivals and departures of domestic passengers at Yogyakarta International Airport for the period January 2022 – December 2023. Based on the results of data analysis, it is known that the ARIMA model time series forecasting method is the best for predicting the number of arrivals. and domestic passenger departures at Yogyakarta International Airport are the AR (1,0,0) model. This method was chosen because the results were significant, met the white noise requirements and had the smallest MAPE value.